Pengaruh Human Relations dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Citra Prima Media - Nuraini Rasyid; Citrayanti (CV. Creative Tugu Pena, 2024)
This study aims to analyze the influence of human relations and motivation on employee performance at PT. Citra Prima Media. The research method used is quantitative with a survey approach, where data was collected from 50 respondents who were employees of the company. Data analysis was carried out using the Partial Least Squares (PLS) method with SmartPLS software version 3. The results showed that human relations have a significant effect on employee performance with a p-value of 0.010. In addition, motivation also has a significant effect on employee performance with a p-value of 0.000. These findings indicate that good interpersonal relationships and high levels of motivation can significantly improve employee performance. Therefore, companies are advised to continue to develop strategies that support harmonious working relationships and increase employee motivation in order to achieve optimal productivity.